A PTEN variant uncouples longevity from impaired fitness in Caenorhabditis elegans with reduced insulin/IGF-1 signaling - Hae-Eun H. Park (Nature Portfolio, 2021)
Mutations in daf-2/insulin/IGF-1 receptor impair the growth and reproduction of C. elegans but conversely enhance immunity and lifespan. Here, the authors show that a missense mutation in the gene retains the effects on lifespan and immunity and improves motility.